Finite element analysis of steel frame for high rise building structure using ANSYS - Lam, Cheng Yong (2019)
In this research, 3D steel frame was analyzed by manual calculation and also ANSYS program with the probabilistic method. This analysis is to determine the stress, strain, deflection, deformation of the structure and checked accordingly to Eurocode 3 as well. Recently, steel frame is normally used in building due to light, greater durability, erected rapidly and economical. A 3D Lin. Beam 188 of steel element type was choose for the 3D steel frame. Due to the design criteria in designing for tensile, compression and buckling were passed, hence the material and geometry of the steel were satisfied as well for this research. The numerical results show very good agreement with manual calculation results. The real behavior of the structure under the applied loads from the results of simulation. The results of cumulative distribution function, histogram plot, sensitivity plot and simple history plot by 10000 times of simulation for any input and output in probabilistic analysis.